Duolingo Mobile Application for English Listening Skill Improvement of Vocational School Students - Arum sari; Saly Kurnia Octaviani (Journal of English Language and Education, 2022)
Duolingo application in mobile assisted language learning can help students flexibly to learn English listening skills by its game-based features. Meanwhile, listening skill as one of significant language aspects for oral communication purpose is highly required for professional need by vocational senior high school. Therefore, this research was intended to find out the progress of students’ English listening skill in SMK Analis Kesehatan Nasional Surakarta using Duolingo and students’ perceptions toward the mobile application. This study used quantitative research with pre-experimental design and its data collection used pre-test, post-test, and close-end questionnaire. The findings show that scores of students’ pre-test and post-test presented significant improvement of students’ English listening skill. The average students’ pre-test score was 73.25 while the average students’ post-test score was 83.3. It was supported by students’ perception that 90% students gave positive perception to the usage of Duolingo mobile application in their English learning process.